2006
DOI: 10.1021/jp057232a
|View full text |Cite
|
Sign up to set email alerts
|

The π−π Stacked Geometries and Association Thermodynamics of Quinacridone Derivatives Studied by 1H NMR

Abstract: The pi-pi stacked associations of three N,N'-di(n-butyl) quinacridone derivatives, widely used dopants in organic light-emitting diodes, with different sizes of substituents were investigated in solution at various temperatures by (1)H NMR spectroscopy. The pi-pi stacked geometries were estimated by both the magnitudes of peak shifts with concentration and the directions of peak shifts induced by polar solvents. Two patterns of geometries with different pi-pi interaction strengths were found to coexist in solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…48,49 We found that the geometries of the QA dimers are little affected by the lengths of the n-alkyl chains. To simplify calculation and save computational costs, we used different N,N 0 -dimethyl quinacridone derivatives as model molecules which are denoted as QA-C 1 , TM-QA-C 1 , DF-QA-C 1 , and DM-QA-C 1 (Fig.…”
Section: Molecular Models and Stacking Configurationsmentioning
confidence: 79%
See 1 more Smart Citation
“…48,49 We found that the geometries of the QA dimers are little affected by the lengths of the n-alkyl chains. To simplify calculation and save computational costs, we used different N,N 0 -dimethyl quinacridone derivatives as model molecules which are denoted as QA-C 1 , TM-QA-C 1 , DF-QA-C 1 , and DM-QA-C 1 (Fig.…”
Section: Molecular Models and Stacking Configurationsmentioning
confidence: 79%
“…We have previously studied the p-stacking geometries and association thermodynamics of N,N 0 -di(n-alkyl) quinacridone derivatives in solution by NMR. 48,49 The p-p interactions of N,N 0 -di(n-alkyl) quinacridone derivatives possessing larger p-conjugated units could offer stronger driving forces to compel molecules stacking as a faceto-face fashion in both crystal and solution structures, [48][49][50] which enable us to use these compounds as models to study the faceto-face interactions and get further understanding on the nature of p-p interactions. Moreover, both stacking manner and substituent property of quinacridone derivatives affect their luminescent color and charge transport property.…”
Section: Introductionmentioning
confidence: 99%
“…Different directions of the chemical shift displacements were also observed for chloroquine and quinacridone. [16,19] The upfield shifts demonstrated by aromatic ring A and aromatic ring C protons in the favored equiplanar geometry are commonly attributed to the strong interactions between the π systems, as in the case of several polyphenolic compounds. [10] The downfield shifts of the aromatic B and aromatic D ring protons may be attributable to the predominance of ring-current-induced diamagnetic deshielding effects from the opposing aromatic rings.…”
Section: Resultsmentioning
confidence: 99%
“…Non-covalent hetero-assembly of small molecules in solution is currently attracting great attention due to extensive use of this phenomenon in molecular electronics [1][2][3], laser physics [4,5], supramolecular chemistry [2,[6][7][8][9], advanced materials [10][11][12][13], numerous biochemical applications [2,14,15] etc. The key feature of this process is the formation of nanoscale aggregates, which modify the macroscopic physical properties of solute resulting in outcomes of practical importance ranging from discovering of new perspective materials to treatment of human diseases [16].…”
Section: Introductionmentioning
confidence: 99%